Diagnostic de l’Etat de Fertilité des Sols Sous Culture Cotonnière Dans les Principaux Bassins de Production de Côte d’Ivoire - Emmanuel N’Goran Kouadio; Emmanuel Kassin Koffi; Kouakou Brou Julien; Gustave Francis Messoum; Kouamé Brou; Dominique Brou N’guessan (European Scientific Journal, ESJ, 2018)
The study was conducted to assess the fertility potential of cotton soilsin Côte d’Ivoire. A total of 500 plots of cotton farmers in 5 regions of thecotton basin was selected for soil sampling in the horizon 0-20 cm. Thechemical analyzes of soil samples in the laboratory were performed on thefollowing parameters: particle size, pHwater, organic matter, total N, availableP, K, Ca, Mg and Cation Exchange Capacity (CEC) of soil. The physicalcharacterization revealed that the studied soils are mainly sandy texture in thesurface horizon. This gives them a very low retention capacity. The chemicalcharacterization of soils showed that they have reactions ranging from slightlyacid to neutral (6.4 <pH<7). These soils have very low levels of total organicmatter, total nitrogen, available phosphorus (in northern, south-central andwestern regions), calcium, potassium, and low values of cation exchangecapacity.